Post- positivism Research Paradigm and Philosophical Assumption of Sport Tourism - Tripathi, Krishna Prasad; Giri, Surendra; Tripathi, Narayan (AWADHARANA, 2024)
A paradigm represents an all-encompassing set of beliefs, perspectives, or structures that direct research and practical applications within a particular field. Different paradigms have different ontological, epistemological, axiological, and methodological descriptions. Every paradigm has differing assumptions of reality and knowledge in which the researcher underpins his or her research approach; this is reflected in their methodology and methods. Post-positivism believes in multiple realities and perceptions by multiple persons in multi social structures in multi-level. Ontology is the researcher's perception, belief, experience, and value of the topic. The ontology of sports tourism asserts a single, real impact of sports events on tourism, though this impact is understood as probabilistic and imperfectly known. Epistemology establishes a philosophical foundation for determining feasible knowledge types and serves as the method by which the researchers perceive sufficient and valid knowledge. It is deep rooted and socially constructed multiple reality in nature. The epistemological knowledge in sports tourism is seen as approximative and tentative, derived through objective, though inherently partial, data collection and analysis. Researchers strive for objectivity while acknowledging and transparently reporting the influence of their values and biases in sports tourism from axiological perspectives. Observation and focused group discussion can be used for qualitative information. Methodology in sports tourism employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to approximate reality.